Pengaruh Media Massa Terhadap Budaya, Sosial dan Ekonomi Masyarakat - zulfikar (At-Tabayyuun: Journal Islamic Studies, 2019)
The strength and degree of the influence of mass media on the cultural, social and economic at least illustrated by assuming a number of theories of the effects of mass media were presented by experts in mass communications in since the beginning of the mid-1960s, following the presence of media technologies of television and radio complement newspaper media earlier in United States of America. Scientific research conducted then, both in the US alone as well as in third countries only reinforces the assumption of previous theories, namely that the influence of the mass media in people's lives more and can not be negotiable, even the mass media offers new ideology, understand the new, new lifestyles and so on. People increasingly can not avoid myself from media exposure, but only one option to adjust in order to include media literacy audiences, so as not to be swayed by media coverage